Executive Function in Preschool-Age Children: Integrating Measurement, Neurodevelopment, and Translational Research. 2016
DOI: 10.1037/14797-004
|View full text |Cite
|
Sign up to set email alerts
|

Structure, measurement, and development of preschool executive function.

Abstract: Human behavior is partly determined by instincts, reflexes, and impulses, but it is also largely driven by the goals that one wishes to reach. Goal attainment may conflict with instincts and automatic responses, and as such, requires intentional regulation of thoughts and actions, which is commonly referred to as executive function (EF). EF allows individuals to respond flexibly and adaptively to an ever-changing environment and thus is effortful, is a complex tertiary process, and matures in a protracted mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 67 publications
2
29
0
1
Order By: Relevance
“…Furthermore, Howard et al (2015) reported that EFs followed dynamic developmental trajectories every 6 months across the preschool period, and did not become linearly more differentiate, as was largely theorized by factorial studies. Moreover, Nelson et al (2016) found that the degree of unity of EFs during these years did not decrease linearly over time.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, Howard et al (2015) reported that EFs followed dynamic developmental trajectories every 6 months across the preschool period, and did not become linearly more differentiate, as was largely theorized by factorial studies. Moreover, Nelson et al (2016) found that the degree of unity of EFs during these years did not decrease linearly over time.…”
Section: Introductionmentioning
confidence: 89%
“…In contrast, Nebraska Barnyard, Big-Little Stroop, Go/No-Go, and Snack Delay showed relatively consistent correlations with each other across the preschool age range, suggesting that they may be more reliable indicators of EC. Collectively, EC, processing speed and the language covariate explained 15–82% of the variance in children's performance on these measures at different ages, whereas the maximum amount of variance explained in studies where our group has modeled EC without accounting for overlap with processing speed at the manifest level is only 57% (Nelson et al, 2014 ; see Willoughby et al, 2013 for similar findings).…”
Section: Discussionmentioning
confidence: 65%
“…At a broad, configural level, the shared variance from a repeatedly administered battery of executive tasks is best modeled as a unitary EC construct regardless of assessment point. At a more nuanced level, this EC factor does not show longitudinal metric or scalar invariance; there are changes in the way that executive tasks relate to the EC construct and in the degree of measurement error over time (Nelson et al, 2014 ). Cascade models suggest that growth in processing speed frees cognitive resources that then can be devoted to higher-order EC (Case et al, 1982 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy and reaction time are useful indicators of EF in that they provide a continuous metric of performance on cognitively challenging tasks that tap EF skills. Particularly ideal for younger children, these measures may be less prone to the floor or ceiling effects that are common in many behavioral measures (e.g., Nelson, James, Chevalier, Clark, & Espy, 2016). In each model, we estimated the unique effect of maternal working memory capacity on child performance in each Go/No-Go task and included child age, child gender, and maternal education as control variables.…”
Section: Methodsmentioning
confidence: 99%